Sulfoxaflor: a new insecticide molecule effective against planthoppers in rice - Bhanu, K Vasanta; Rao, N Mallikharjuna; Lakshmi, M Bharata (Indian Journal of Plant Protection, 2020)
Field experiments were conducted during Kharif 2011 and Rabi 2011-12 at Andhra Pradesh Rice Research Institute and Regional Agricultural Research Station, Maruteru to evaluate the comparative effectiveness of sulfoxaflor 24 SC against planthoppers (brown planthopper and white backed planthopper) in rice. Sulfoxaflor 24 SC at both the dosages tested viz., 75 and 90 g a.i/ha reduced the buildup of planthoppers in both the seasons and was superior to other insecticides with a mean per cent reduction of planthoppers population by 88.0 and 85.7, respectively during Kharif 2011 and 74.3 and 84.4 respectively, during Rabi 2011-12, over the untreated control. The other insecticides, Sutathion 40 EC and Hostathion 40 EC @ 300 and 500 g a.i./ha recorded significantly higher number of planthoppers than untreated control in both the seasons indicating that they may cause resurgence of planthoppers. In addition to reduction in planthoppers population, sulfoxaflor 24 SC at both the dosages tested, recorded significantly lower per cent of white ears and superior grain yields in both the seasons.